Survey on Flame Detection by Optical Flow Estimation - Thomas, Anju; Azath, M (International Journal of Computer Sciences and Engineering, 2014)
Automatic fire detection by real time vision based method got great importance in recent years. By the development in science and technologies it has drawn potential significance in last decades. There are different video based detection for smoke, fire and object’s movement .The importance of fire being detected as early as possible is to take prevention and precaution before it causes any material damage, human casualties. Survey aims to study the different methods and techniques used for flame detection and some related works.